Systematic IEEE rounding method for high-speed floating-point multipliers. - Quach, N.T (IEEE Transactions on VLSI systems)
For performance reasons, many high-speed floating-point multipliers today precompute multiple significand values (SVs) in advance. The final normalization and rounding steps are then performed by selecting the appropriate SV. While having speed advantages, this integrated rounding method complicates the development of the rounding logic significantly, hence, requiring a systematic rounding method. The systematic rounding method, presented in this paper, has three steps: 1) constructing a rounding table; 2) developing a prediction scheme; and 3) performing rounding digits selection (RDS). The rounding table lists all possible SVs that need to be precomputed. Prediction reduces the number of these SVs for efficient hardware implementation while RDS reduces the complexity of the rounding logic. Both prediction and RDS depend on the specifics of the hardware implementation. Two hardware implementations are described. The first one is modeled after that reported by Santoro et al. and the second improved one supports all IEEE rounding modes. Besides allowing systematic hardware optimization, this rounding method has the added advantage that verification and generalization are straightforward.